2012
DOI: 10.1021/jp306241p
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Ion Diffusion in Ionic Liquid Studied by Electrochemical Scanning Electron Microscopy with X-ray Fluorescence Spectrometry

Abstract: Investigating metal-ion transport in ionic liquid media is important to realize batteries and electrodeposition, which utilize intriguing properties of the media. An in situ electrochemical scanning electron microscopy together with X-ray fluorescence spectrometry is developed by a simple modification of an instrument as a tool for the investigation. Diffusion of silver ions (Ag + ) in an ionic liquid 1-butyl-3-methylimidazolium trifluoromethanesulfonylamide (BMI-TFSA) is monitored as the time variation of Ag … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…Room-temperature ionic liquids (RTILs), which are liquid salts consisting only of cations and anions, have fascinated many researchers in various fields because of their unique physicochemical properties such as incombustibility, high ionic conductivity, high thermal stability, and wide electrochemical window. Among these properties, the negligible vapor pressure of RTILs is one of the most important features in recent research using RTILs under vacuum conditions. , Our research group developed several new technologies that can be categorized as RTIL-vacuum technology. , For example, we have developed an in situ scanning electron microscopy (SEM) technique to investigate electrochemical reactions in RTIL concurrently with the polarization of electrodes. , In a series of investigations, we further noticed that certain types of chemical reactions, i.e., the reduction of metal ions, are induced by electron beam irradiation. , The first finding was that gold particles were produced in an RTIL that contained gold ions during the observation of the RTIL by SEM. On the basis of these perceptions, we have established a completely new method to fabricate micro/nanosized polymer structures by drawing arbitrary patterns on a polymerizable RTIL, 1-allyl-3-ethylimidazolium bis­((trifluoromethane)­sulfonyl)­amide ([AllylEtIm]­[Tf 2 N], Scheme ), with a focused ion beam (FIB) instrument .…”
Section: Introductionmentioning
confidence: 99%
“…Room-temperature ionic liquids (RTILs), which are liquid salts consisting only of cations and anions, have fascinated many researchers in various fields because of their unique physicochemical properties such as incombustibility, high ionic conductivity, high thermal stability, and wide electrochemical window. Among these properties, the negligible vapor pressure of RTILs is one of the most important features in recent research using RTILs under vacuum conditions. , Our research group developed several new technologies that can be categorized as RTIL-vacuum technology. , For example, we have developed an in situ scanning electron microscopy (SEM) technique to investigate electrochemical reactions in RTIL concurrently with the polarization of electrodes. , In a series of investigations, we further noticed that certain types of chemical reactions, i.e., the reduction of metal ions, are induced by electron beam irradiation. , The first finding was that gold particles were produced in an RTIL that contained gold ions during the observation of the RTIL by SEM. On the basis of these perceptions, we have established a completely new method to fabricate micro/nanosized polymer structures by drawing arbitrary patterns on a polymerizable RTIL, 1-allyl-3-ethylimidazolium bis­((trifluoromethane)­sulfonyl)­amide ([AllylEtIm]­[Tf 2 N], Scheme ), with a focused ion beam (FIB) instrument .…”
Section: Introductionmentioning
confidence: 99%
“…We found that magnetron sputtering onto RTIL yields a wide variety of metal and alloy nanoparticles without any stabilizing agent 23 24 and that RTIL itself can be observed by a scanning electron microscope without accumulation of electrostatic charge at the surface of RTIL 25 . The latter is applicable to scanning electron microscope (SEM) and transmission electron microscope (TEM) observations of hydrated specimens pretreated with RTIL and to in situ SEM observation of chemical reactions in RTIL 26 27 28 29 .…”
mentioning
confidence: 99%
“…The local concentration of Li þ has been estimated indirectly by the Raman spectra and the optical absorption of a counter anion [26,27], and directly by 7 Li NMR spectra [25]. Li þ is not detectable by the fluorescent X-ray method, although the direct observation of the concentration distribution of silver species in an ionic liquid has been also reported using a scanning electron microscope with an energy dispersive X-ray analysis [28]. While the concentration distribution can be visualized by these methods, the time required for these measurements is generally longer than that for EQCM.…”
Section: Resultsmentioning
confidence: 99%